MUSLIM STUDENT’S DECISION IN BUYING HALAL PRODUCTS - Bachri, Naufal (CV. Radja Publika, 2023)
This study aims to examine the influence of halal label, lifestyle, and brand image on Muslim student’s decision in buying halal skincare in the Kota Lhokseumawe. Besides that, this study wants to know the dominant factors that influence halal skincare decision. Primary data was collected using a structured questionnaire of 120 respondents. This structured questionnaire has been tested for validity and reliability. The sampling technique used is purposive sampling approach. The data analysis method used is multiple linear regression with the help of SPSS Software. The results of the study indicate that halal label, lifestyle, and brand image have positive dan significant effect on Muslim student's decisions in buying halal skincare products in Kota Lhokseumawe. However, factor of lifestyle is the main determining element in making decision to buy halal skincare in Kota Lhokseumawe. This finding has implication for the development of the concept of halal products and consumer behavior.